The application of GSP 48 in dealing with divorce cases related to witchcraft - Mahyuddin, Ismail; Mansor, Sulaiman; Nurkarimah, Yusof; Faizal, Abdul Khir; Zainal Abidin, Kusmin; Yuhaniz, Mohd Yusop (2019)
Allah SWT mentioned in Al-Quran (2: 102) that there are people who learn sihr (black magic) and use it to cause marital separation. In fact, such issue was raised in several divorce cases at Shari’ah Court in Malaysia. Nevertheless, the absence of legal mechanism on how to deal with the issue has caused it to be left unattended. In 2016, a group of researcher from UMP, through the Exploratory Research Grant Scheme (ERGS) project, has developed an instrument which is called GSP 48 to measure the authenticity of such claim and has also developed procedure on how to deal with it. The finding is very useful since it may help the religious and legal institution to save a marriage from the witchcraft evilness. In collaboration with JAKIM, an on-going knowledge transfer program has been conducted recently exclusively for all Registrars of Marriage, Divorce and Ruju’ from all states in Malaysia. This project aims to expose, teach and train these officers on how to deal with the cases by using GSP 48. The 1st workshop was held from 18-20th of September 2019. In this program, participants were trained on how to apply the GSP 48 instrument and its procedures. As a result, the participants discovered that divorce caused by sihr can be properly managed and solved through legal mechanisms. Most of the participants are interested to apply the GSP 48 and its procedures in their work practices.